Evaluasi Penerapan Akuntansi Untuk Kontrak Asuransi Pada PT. Asuransi Allianz Life Indonesia - Dwi Urip Wardoyo; Adelia H. Adisty; Celka Gesilka; Gita M. Hutagaol (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Insurance is an institution that plays an important role in the economy. This study aims to analyze the application of financial accounting standards namely PSAK 62 (2015) regarding insurance contracts at PT. Asuransi Allianz Life Indonesia. This study uses qualitative methods with content analysis. The data used in this study is sourced from the official website of the relevant company, the data used as a sample are the financial statements of PT. Asuransi Allianz Life Indonesia from 2019 up to 2020. The analysis of this research was conducted on the presentation and disclosure of the company's financial statements adjusted to the provisions of accounting standards and applicable regulations. The results of this study indicate that PT. Asuransi Allianz Life Indonesia has implemented the recognition, measurement, and presentation of premium income, claims and acquisition costs applied by those following PSAK 62 (2015).